Peace Education of the Sarung-Wearing Community: Nahdlatul Ulama Kiai’s Efforts in Managing Interfaith Diversity through Alternative Education - Herawati, Erna; Fauzi , Soni; Hikmah, Nurul; Ningtiyas, Ratih Kusuma (Postgraduate Program, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2023)
This article examines the pivotal role played by Nahdlatul Ulama (NU), an Islamic organisation in Indonesia, in embracing religious and cultural diversity through alternative education. The study concentrates on the efforts of NU Kiais (religious leaders) in the Kasembon House of Worship, Malang, in fostering harmony among religious communities and creating a peaceful environment through education. Adopting a specific approach, this peace education not only concentrates on academic learning but also on the formation of character based on humanitarian values, tolerance, and respect for religious differences. This article employs a descriptive-analytical approach to examine the strategies employed by NU Kiais to promote peaceful education. Through interviews, observations, and document analysis, this research identifies specific actions undertaken by Kiais to foster inclusive perspectives and a deeper comprehension of religious values and human universality. The findings indicate that the alternative education provided by NU Kiais has effectively created an environment conducive to interfaith dialogue, enhanced mutual understanding, and facilitated cross-faith collaboration.